The susceptibility of leopards Panthera pardus to trophy hunting - Braczkowski, A (2013)
The trophy hunting of African leopards Panthera pardus pardus may generate revenue to help foster their conservation. However, leopards are sensitive to hunting and populations decline if overharvested. The practice therefore requires careful management grounded in robust estimates of population density/status. Camera-trap surveys are commonly used to establish leopard numbers, and may guide harvest quotas. However, such surveys are limited over wide spatial scales and many African governments lack resources to implement them. In this thesis I explore the potential use of a harvest composition scheme applied to puma Puma concolor in North America, to monitor leopards. The method hinges on the susceptibility of different leopard cohorts to hunting and if this varies, then predictions can be made about harvest composition. Susceptibility is likely to be governed by space use, encounter rates with bait lures (a common method used to attract leopards to hunting hides) and hunter selectivity. Thus in this thesis I explore leopard susceptibility to these factors using a protected leopard population in northern Zululand, South Africa. In my first chapter I examine using scent lures in camera-trapping. Against a backdrop of a passive survey I show adult males, females and sub-adults are captured at similar rates compared to a passive survey using lures. The use of lures does not appear to violate closure assumptions or affect spatio-temporal patterning, but their use appears limited as density estimate precision is not improved. My second chapter examines ecological (likelihood of encountering a hunter) and anthropogenic (attractiveness to hunters) susceptibility of leopards to trophy hunting. I show that adult males are the most susceptible cohort to hunting (sub-adults least susceptible). I then take the incident rates from ecological and anthropogenic models and create a theoretical harvest composition using population parameters of protected leopards. My third data chapter departs from hunting susceptibility and examines determinants of leopard trophy package price across Africa. I show that factors such as trophy quality, outfitter leopard hunting reputation and hunt success have little impact on price determination. Instead, overall outfitter reputation and the number of charismatic species in a package are positively correlated with price. These results have important consequences on several sustainable leopard hunting schemes proposed in the literature.